The use of arnica tablets by runners in the 90 kilometer Comrades Marathon - Cynthia M. Bauer; Michael I. Lambert; Lindsay M. Weight (AOSIS, 2001)
Background: Arnica is a homeopathic remedy which is sometimes used before and after long distance running in the belief that it reduces delayed onset muscle soreness (DOMS). However, the specific details of its use among athletes is not known. Therefore the aim of this study was to determine the usage patterns of Arnica tablets amongst participants in the 1999 ninety-kilometer Comrades ultra-marathon road race in South Africa. Methods: Every third runner registering for the race in Pietermaritzburg in the three-day (25 hour) pre-race registration period was approached and asked to complete a questionnaire on their use of Arnica tablets (n - 785; males = 85% and females = 15%). Results: Ten percent of the total study population who agreed to participate in the study (n = 730) had used Arnica tablets in the previous six months. The average reported dose by these athletes was seven tablets per day. The most common reason for using Arnica tablets was to decrease pain or stiffness after a race or training run. Only a small group (22%) rated the efficacy of Arnica tablets as "totally effective", suggesting that a large number of users of Arnica did not rate the efficacy highly. There was a poor relationship between the perceived efficacy after ingesting Arnica tablets and the reported dosage (r = 0.28). The majority of the respondents (63%) believed that Arnica tablets contained anti-inflammatory agents. Conclusions: While 10% of the runners used Arnica, only one fifth of these runners rated the treatment as completely effective for the prevention of DOMS. Therefore education on the advantages and disadvantages of using these tablets has become important.